Contribution and strategies for the prevention of penile cancer in primary health care - Santos, Larissa Christiny Amorim dos; Ribeiro, Wanderson Alves; Castro, Kemely de; Cirino, Hosana Pereira; Ribeiro, Matheus Sampaio; Morais, Maicon Costa de; Dias, Lilian Laine da Conceição; Freire, Maria Júlia Louvain Longo (Brazilian Journal of Science, 2022)
Despite the cultural idealization about masculinity and invulnerability, men are getting sick more and more. Penile neoplasia is one of the diseases that has been affecting men in different prevalences, even though it is a disease with variable forms of prevention. Therefore, the study aims to point out the preventive actions implemented by nurses in the health of the male population related to penile cancer. This is an integrative literature review study with a time frame between 2018 and 2022. The results indicate that, despite penile cancer having a low prevalence in a general scope, it still has worrying indicators, when comparing developed and developing countries. It is concluded that the theme presented contributes and encourages good practices on the part of nurses and users of health services. It also stimulates the learning process and vision of educational institutions, helping and promoting knowledge and taking it in a clear and objective way, aiming at the well-being of the population, and also lists the fundamental role of nurses in preventive intervention for penile cancer.